Historical understanding of science - Orozco Contreras, Richard Antonio (2015)
In this brief essay, the author will explain in some detail the formation of science from understandingthat epistemology makes it. He sees, however, only four key moments: their formation, the modernrevolution, the scientism of the nineteenth century, and finally the contemporary epistemology.The author chooses this moment, not arbitrary, but because they are considered really significantto understand what science is today.